PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK PADA KD PERKEMBANGAN KOLONIALISME DAN IMPERIALISME MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION KELAS VIII-A SMP N 7 PURWOREJO SEMESTER I TAHUN PELAJARAN 2016/2017 (Harmony: Jurnal Pembelajaran IPS dan PKN, 2019)
The objectives of this study are: (1) to describe the increase in the activities of grade VIII-A students after participating in the Cooperative Integrated Reading and Composition learning competency model of colonialism and imperialism, (2) describing the increasing competency in the development of colonialism and imperialism after applying the Cooperative Integrated learning model Reading Composition of students in class VIII-A SMP Negeri 7 Purworejo Semester I of 2016/2017 Academic Year. The research design of Kemmis and Mc Taggart's model consisted of two cycles. Each cycle has four stages, namely planning, action, observation and reflection. The research subjects were students of class VIII-A of SMP Negeri 7 Puworejo with a total of 32 students. Data collection techniques used methods: tests, observations, documentation and interviews. Data analysis uses descriptive qualitative and quantitative data analysis. The results of the increase in learning activities can be seen from each cycle, namely in the first cycle the percentage of learning activities of the average students of 58% in the criteria is quite active while in the second cycle rose 28% to 86% in the very active criteria. Student learning competency has increased. The number of value acquisition increased from 2,475 in the initial conditions to 2,780 in cycle II. The highest value of 100 in the initial conditions, cycle I and cycle II. Mastery learning increased from 19 people to 24 people in the first cycle, an increase of 5 compared to the initial conditions. At the end of the second cycle completeness learning to 29 people experienced an increase of 5 people compared to cycle I. The average value of the class increased 9.53 from the initial condition of 77.34 to 86.87 in the second cycle. There is an increase in completeness of classical learning from the initial conditions to cycle I, cycle I to cycle II. From the initial conditions to the first cycle there was an increase in the percentage of completion of learning from 59.37% to 75% in the first cycle, from the first cycle to the second cycle there was an increase in the percentage of completion of the study from 75% to 90.63%, so that the percentage increase in completion of the study the beginning of the second cycle there was an increase of 31.26% Tujuan penelitian ini adalah: (1) mendeskripsikan peningkatan aktivitas peserta didik kelas VIII-A setelah mengikuti proses pembelajaran dengan model Cooperative Integrated Reading and Composition kompetensi perkembangan kolonialisme dan imperialisme peserta didik kelas VIII-A SMP Negeri 7 Purworejo Semester I Tahun Pelajaran 2016/2017, (2) mendeskripsikan peningkatan kompetensi perkembangan kolonialisme dan imperialisme setelah diterapkannya model pembelajaran Cooperative Integrated Reading Composition pada peserta didik kelas VIII-A SMP Negeri 7 Purworejo Semester I Tahun Pelajaran 2016/2017. Penelitian ini merupakan penelitian tindakan kelas, desain penelitian model Kemmis danMc Taggart yang terdiri dari dua siklus. Setiap siklus memiliki empat tahap yaitu perencanaan, tindakan, pengamatan dan refleksi. Subyek penelitian adalah siswa kelas VIII-A SMP Negeri 7 Puworejo berjumlah 32 orang siswa.Tehnik pengumpulan data menggunakan metode: (1) Tes, (2) Observasi, (3) Dokumentasi dan (4) wawancara. Analisis data menggunakan analisis data deskriptif kualitatif dan kuantitatif. Hasil penelitian :proses pembelajaran berjalan dengan kondusif. Hasil peningkatan aktivitas belajar dapat dilihat dari masing-masing siklus, yaitu pada siklus I persentase aktivitas belajar peserta didik rerata 58% dalam kriteria cukup aktif sedangkan pada siklus II naik 28 % menjadi 86 % dalam kriteria sangat aktif. Kompetensi belajar peserta didik mengalami peningkatan.Jumlah perolehan nilai meningkat dari 2.475 pada kondisi awal menjadi 2.780 pada siklus II. Nilai tertinggi dari 100 pada kondisi awal, siklus I dan siklus II. Ketuntasan belajar terjadi peningkatan dari 19 orang menjadi 24 orang pada siklus I, meningkat 5 orang dibandingkan kondisi awal. Pada akhir siklus II ketuntasan belajar menjadi 29 orang mengalami peningkatan 5 orang dibandingkan siklus I.Nilai rata-rata kelas meningkat9,53dari kondisi awal 77,34 menjadi 86,87 pada siklus II. Terdapat kenaikan ketuntasan belaja rklasikal dari kondisi awal terhadap siklus I, siklus I terhadap siklus II. Dari kondisi awal terhadap siklus I terdapat kenaikan persentase tuntas belajar dari 59,37% menjadi 75% pada siklus I, dari siklus I terhadap siklus II terdapat kenaikan persentase tuntas belajar dari 75% menjadi 90,63%, sehingga kenaikan persentase tuntas belajar dari kondisi awal tehadap siklus II terdapat kenaikan sebesar 31,26%.